Pengaruh Gaya Kepemimpinan Demokratis Dan Motivasi Terhadap Semangat Kerja Karyawan Pada Pt. Kallista Prima Cabang Denpasar - Diah Utari, Ni Made Ayu Savitri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
There are still performance targets that have not been achieved at PT. Kallista Prima Denpasar Branch is due to the employee's lack of morale in completing their respective jobs, because employees feel that there is still a lack of bonuses given by the company for the work they have done. The decline in employee morale actually greatly affects sales turnover within the company. Based on this, the purpose of this study was to determine the effect of democratic leadership style and motivation on employee morale at PT. Kallista Prima Denpasar Branch. This research uses quantitative and qualitative data types. The population in this study were all employees of PT. Kallista Prima Denpasar Branch by determining the sample using the Non-propability technique, namely a saturated sample of 40 people. Collecting data using a questionnaire that was tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study indicate that: (1) Democratic Leadership Style has a positive and significant effect on the work spirit of PT. Kallista Prima Denpasar Branch, (2) Motivation has a positive and significant effect on the work spirit of PT. Kallista Prima Denpasar Branch, (3) simultaneously democratic leadership style and motivation have a positive and significant effect on morale at PT. Kallista Prima Denpasar Branch.